Cascavel e suas memórias: uma análise discursiva da cidade e seus monumentos. - KLIN, Thiago Viniícius (2023)
This study focuses on the city of Cascavel, in western Paraná, exploring the rich architectural materiality present in its squares, monuments and, in particular, along Avenida Brasil. Through the lens of Discourse Analysis, as proposed by Michel Pêcheux, the research aims to understand the significance of the representations and discursive meanings of these structures in the formation of local collective memory. The central objective is to uncover how intrinsic memories, manifested in works of art, architecture and monuments, contribute to the cultural identity of the inhabitants of Cascavel. By monumentalizing these elements, the aim is to capture the essence of the narratives that permeate everyday urban life, highlighting the importance of the city as a symbolic space for the production of meaning. Using Discourse Analysis, this paper sets out to observe the symbolic dimension of the city, going beyond its demographic function to understand how Cascavel establishes itself as an articulator of memories and identities. Enilda Orlandi and Magda Ferreira are cited to support the discussion on the urban and its ability to generate meanings. The results point to the importance of recognizing and preserving Cascavel's cultural heritage, not just as a set of physical structures, but as an interweaving of stories and meanings that reflect and shape the lives of Cascavel residents.